Retailerâ€™s Perspective on Support Services Offered by Vembanad White Cement - S, Satya (Journal of Economics and Behavioral Studies, 2011)
Buying behavior of consumers in Cement industry is greatly influenced by retailers as they are the last point in the distribution channel and have a direct understanding of consumerâ€™s requirements. The retailers experience firsthand reactions of customers on product, services and quality assessments. In practice, it is very easy for a retailer to impress on the customer with a change in brand even at the very last moment. Because cement retailing is not exclusive and variety of competitive brands is available in the same outlet, it is important that the manufacturing company take great efforts to satisfy the retailers and keep their â€œsupport service levelsâ€ very high. The research through a field survey explores retailerâ€™s perspective on support services offered by Vembanad White Cement. Suggestions are given to the company on increasing support services to the retailers through efficient complaint handling, credits and processing speed to enable smooth transactions between the retailers and the customers. Retailerâ€™s satisfaction would influence buying behavior of end customers in a positive way. Proactive and personal approach from the company will make the retailers take interest to pass positive feedbacks to the consumers on product and its quality. In the buying process, recommendations from the retailers are the final step in sealing sales with the customers. Hence it is important to understand the retailerâ€™s suggestions for improvements in service levels. Implementing these improvements will not only promote positive attitude of the retailers, in turn, it will also pass on as positive word of mouth to the customers encouraging larger client base and profits to the company.